THE EFFECTS OF USER-GENERATED REVIEWS VERSUS INFLUENCER-GENERATED REVIEWS ON CONSUMER PURCHASE INTENTION - Puspitasari, Almira Vania; Aruan, Daniel Tumpal H. (Universitas Brawijaya, Indonesia, 2023)
As the use of mobile devices increases, social media and online reviews are increasingly important in the spread of WOM and play an important role in consumer decisions and the consumer journey. Companies can take advantage of online reviews in the form of User-Generated Reviews (UGR) and Influencer-Generated Reviews (IGR) to improve marketing strategies. This study aims to determine which online review is more effective between user-generated and influencer-generated reviews. The authors use experiments to examine how the type of online review (UGR vs IGR) influences consumers' perceptions of reviews and purchase intentions. This study predicts differences between the two online reviews influencing consumer purchase intentions. This research used an experimental design, and primary data collection was carried out with a web-based questionnaire. This study found that influencer-generated reviews were more effective in influencing purchase intentions. Interestingly, this is due to a process in which consumers assume IGR is more effortful to craft and subsequently equate this greater perceived effort with the credibility of the review and leading to more persuasive, in effect, purchase intention. Given the increasing use of mobile devices, social media, and the increasingly important online reviews (UGR and IGR) in the spread of WOM, this research contributes to understanding consumer decision-making processes and journeys when processing online reviews.